2021
DOI: 10.1088/1755-1315/782/4/042035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biofertilizer, chicken manure and dolomite on chemical soil and the growth of soybean at potential acid sulphate soils

Abstract: The combination of Biotara bio fertilizer and dolomite is known to improve the potential acid sulphate soil fertility. This research has been carried out to examine the effect of Biotara as bio fertilizer, chicken manure, and dolomite on several soil chemical properties and soybean growth in potential acid sulphate soil from May 2018 to January 2019 at greenhouse of Agricultural Faculty, Universitas Sumatera Utara Medan. This research has been carried out using factorial randomized block design with 2 (two) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Sweet potato plants treated with 42 tons of chicken manure per hectare on acid soils significantly increased the yield index, namely 0.24. The results of [5,12] also showed that the application of manure increased the sweet potato harvest index. The application of manure can increase the uptake of nitrogen, phosphate, potassium, calcium, and magnesium, provide biodegradable organic matter that can increase soil aggregation thereby improving soil physic-chemical conditions such as soil water holding capacity, creating a conducive environment for root development to increase yields.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Sweet potato plants treated with 42 tons of chicken manure per hectare on acid soils significantly increased the yield index, namely 0.24. The results of [5,12] also showed that the application of manure increased the sweet potato harvest index. The application of manure can increase the uptake of nitrogen, phosphate, potassium, calcium, and magnesium, provide biodegradable organic matter that can increase soil aggregation thereby improving soil physic-chemical conditions such as soil water holding capacity, creating a conducive environment for root development to increase yields.…”
Section: Resultsmentioning
confidence: 88%
“…It is necessary to conduct research on the use of local resources in managing acid soil [4]. Several researchers reported using chicken manure to increase soil pH, organic matter content, and nutrient availability [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of P1 biofertilizer substituted the application of NPK fertilizer by 50% and increased yield by 30% compared to control (without biofertilizer). According to study by Lubis et al (2021) the application of biofertilizer and chicken manure increased organic C, total N, availability of P in acid sulfate soils and increased N and P uptake by soybeans.…”
Section: Soybean Growth and Productivitymentioning
confidence: 99%
“…Treatment P2 contains decomposers, P-solubilizing bacteria, and N 2 -fixing bacteria (Azospirillum sp.) which are inoculated from swampland (Lubis et al, 2021). This causes that the N 2 -fixing microbes in P2 biofertilizers be more adaptable compared to P3 biofertilizers.…”
Section: Microorganism Populationmentioning
confidence: 99%
“…Biochar has the effect of neutralizing the pH which was initially slightly acidic to neutral, but to get a neutral pH on acidic soil requires repetition every third season [18]. The application of the dolomite dosage at about 2 tons ha -1 and 4 tons ha -1 can increase height and dry weight of soybean and also increase N and P uptake of soybean [19].…”
Section: Component Yield and Grain Yieldsmentioning
confidence: 99%